Constraints in the Numerical Modelling of Salt Water Intrusion - Kumar, C.P. (Journal of Soil and Water Conservation, 2022)
Mathematical models help us to understand the relevant processes that cause salt water intrusion ion in coastal aquifers. In this paper, constraints of three-dimensional (3D). variable density modelling of salt water intrusion in large-scale coastal (homogeneous) aquifers have been discussed. Computer codes, which solve the advection-dispersion equation based on standard finite element or finite difference techniques. can not yet be applied to model large-scale coastal aquifers. The reason is that these codes must satisfy a condition of spatial discretization, characterized bv the so-called grid Peelet number. This number imposes that the dimension of the grid block should be not greater than a few times the magnitude of the longitudinal dispersivity, as otherwise numerical dispersion will occur. In addition, stand-alone personal computers are not yet fast enough to execute models with several hundreds of thousands of grid blocks. Finally, reliable and sufficient groundwater data, required for calibration and verification, are not available in most cases. However, effective 3D-modelling of salt water intrusion in large-scale coastal aquifers may be technically possible within next few years, though the availability of data will always restrict practical applications to a certain extent.